(untitled) (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2023)
The objective of this research article is to analyze the sociocultural factors of women victims of domestic violence in the municipality of Soledad in the department of Atlántico, Colombia. The methodology used was based on the positivist paradigm, the type of research was descriptive, the design is transversal, non-experimental and field; The population consisted of 272 and the sample of 66 women. The data were collected with a Likert-type scale questionnaire, the data were analyzed with descriptive and inferential statistics. The results indicate an average of 3.07 in the sociocultural factors of the female victim of domestic violence, located in the moderate category. It was concluded that women victims of this scourge sometimes present inappropriate sociocultural behaviors.